THE OCCURRENCE OF SEPTIC ARTHRITIS IN CALVES: BACTERIAL ISOLATION AND THEIR ANTIBIOTICS SENSITIVITY PATTERNS - J. Kallo, 0.; A. Zaidan, H.; K. Delaimi , A. (The Iraqi Journal of Veterinary Medicine, 1994)
This study was carried on 50 calves with septic arthritis. Synovial effusion was obtained by arthrocentesis from the joints of these calves and examined bacteriogically to determine the antibiotic sensitivity patterns of the isolates to 14 antibacterial agents. The results showed that the incidence of septic arthritis was higher in male calves (74%) than in females (26%). The higher incidence was found in calves under two months of age. The most frequent bacterial isolates were Escherichia coli, Klebsiella spp., Proteus mirablis, Corynebacterium pyogenes, beta-haemolytic Streptococcus spp., Staphylococcus aureus and Pseudomonas aeruginosa. It was shown that most of gram positive isolates were susceptible to ampicillin, cloxacillin, erythromycine, fucidin, garamycin and pencillin. Pseudomonas aeruginosa was the most resistant microorganism to all antibiotics used except amikac in and garamyc in.